Intima-media thickness and large artery elasticity in patients with ischemic chronic heart failure - N. A. Kosheleva; A. P. Rebrov; O. V. Karpova; T. V. Martynova (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To assess intima-media thickness (IMT) of carotid arteries (CA), large artery elasticity, and their effects on clinical prognosis in patients with ischemic chronic heart failure (CHF). Material and methods. The study included 207 patients (mean age 55,1±6,4 years) after myocardial infarction (MI), with CHF symptoms, and 40 healthy controls. The assessment of CA IMT was performed with Acuson 128 XP/10 device; large artery elasticity and stiffness was assessed with arteriograph TensioClinic (TensioMed, Hungary). Results. In CHF patients, increased CA IMT, increased large artery stiffness, and an association between aortic pulse wave velocity (APWV) and CA IMT were observed. APWV values >12 m/s were associated with a significantly higher risk of CHF decompensation (р=0,001), repeat MI (р=0,01), death (р=0,001), and all major cardiovascular events (CVE) (р=0,01), compared to APWV ≤12 m/s. Multivariate analysis results demonstrated that in CHF patients with APWV >12 m/s, one-year risk of CVE was 2,02 times higher than in patients with APWV ≤12 m/s (hazard ratio 2,02; 95 % CI 1,01-4,03). Conclusion. CA IMT was associated with APWV, while the latter was an independent risk factor of CVE in patients with ischemic CHF.